Genomic Characteristics of a Chicken Infectious Anemia Virus in Contaminated Attenuated Vaccine - Chen, Longfei; Su, Qi; Li, Yan; Wang, Jinjin; Zhang, Yawen; Chang, Shuang; Wang, Yixin; Zhao, Peng (Frontiers in Veterinary Science, 2022)
Chicken infectious anemia virus (CIAV) can be transmitted by contaminated live vaccines, and causes huge economic losses. This study evaluated the contamination status of CIAV in 24 batches of vaccines by recombinase-aided amplification assay (RAA), fluorescence quantitative PCR and dot blot assay, and then found a contaminated attenuated vaccine. The whole genome of the CIAV contaminant was then sequenced and named JS2020-PFV (Genbank accession number: MW234428, 2296bp). It showed 94.5% to 99.9% identities with reference strains and shared the closest evolution relationship with AB1K strain which was isolated from a chicken farm in Turkey. All of these suggested that the use of CIAV contaminated live vaccine may be one of the reason for its epidemic in poultry.